Of power and memory within the palestinian-israeli conflict. the israeli action against the “potentis phalestinae” (2010)
The Palestinian – Israeli conflict is a political conflict determined by the use that actors, Israel, the Palestinian National Authority and resistance movements, make of power and its different historic and media manifestations. It is necessary to question on the origin of the problem, particularly when inquiring on the false conception of the Jewish nation as a theoretical corpus, so that way to understand how radicalisms have been crucial in the escalade of aggressions in Palestine. The article revises, consequently, different conceptions of power, searches for their use in the structure of the conflict and ends up with an analysis of the actors’ actions, in terms of power itself.